Boric acid thermal etching graphite felt as a high-performance electrode for iron-chromium redox flow battery - Zhen Li; Lili Guo; Na Chen; Yang Su; Xiaomin Wang (Materials Research Express, 2022)
Iron-chromium redox flow battery (ICRFB) is a secondary battery capable of deep charge and discharge. It is a novel electrochemistric equipment for energy storage. ICRFB has around wide concern as it possesses advanced characteristics such as high energy, long cycle life, and environmental friendly. Graphite felt is a common electrode material for ICRFB because of its high temperature resistance, corrosion resistance, infinite specific surface area, and admirable electroconductibility. However, poor hydrophilicity and electrochemical activity lead to the graphite felt to be modified to be better applied in ICRFB. To improve the electrochemical activity of graphite felt, the PAN-based graphite felt was activated by boric acid thermal etching, and tested with SEM analysis, electrochemical analysis, and charge-discharge test. The results showed that the electrochemical activity and reversibility of boric acid thermal etching graphite felt impregnated with 25% boric acid solution were significantly improved after thermal treatment at 500 °C for 5 h. The Energy Efficiency of boric acid thermal etching graphite felt impregnated with 25% boric acid solution in ICRFB could reach more than 85%, which was about 9.5% higher than that of ICRFB with untreated graphite felt (1#) as electrode.